2004
DOI: 10.1037/0893-3200.18.1.36
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Stress Disorder and Current Relationship Functioning Among World War II Ex-Prisoners of War.

Abstract: This study examined the association of posttraumatic stress disorder (PTSD) with the quality of intimate relationships among present-day male World War II ex-prisoners of war (POWs). Ex-POWs had considerable marital stability; those with PTSD were no less likely to be in an intimate relationship. Ex-POWs in an intimate relationship who had PTSD (N=125 ) were compared with ex-POWs in a relationship who did not have PTSD (N=206). Marital functioning was within a range expected for persons without traumatic expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
199
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(221 citation statements)
references
References 44 publications
19
199
0
3
Order By: Relevance
“…Moreover, specific symptom clusters or components of PTSD such as dissociation (Nelson Goff et al, 2007) and numbing or avoidance symptoms (Cook, Riggs, Thompson, Coyne, & Sheikh, 2004;Erbes, 2011;Renshaw & Campbell, 2011;Riggs et al, 1998) appear to be associated with greater erosion of relationship functioning. Specific problematic areas of relationship functioning for service members struggling with PTSD and their partners have also been identified.…”
Section: Intimate Relationships and Ptsdmentioning
confidence: 99%
“…Moreover, specific symptom clusters or components of PTSD such as dissociation (Nelson Goff et al, 2007) and numbing or avoidance symptoms (Cook, Riggs, Thompson, Coyne, & Sheikh, 2004;Erbes, 2011;Renshaw & Campbell, 2011;Riggs et al, 1998) appear to be associated with greater erosion of relationship functioning. Specific problematic areas of relationship functioning for service members struggling with PTSD and their partners have also been identified.…”
Section: Intimate Relationships and Ptsdmentioning
confidence: 99%
“…Combat or other military-related traumatic experiences may be particularly challenging for the couple (Dirkzwager, Bramsen, Adèr, & van der Ploeg, 2005;Ruger, Wilson, & Waddoups, 2002), contributing to secondary traumatic stress symptoms in partners (Figley, 1983(Figley, , 1995Nelson Goff & Smith, 2005) and impaired couple relationship functioning (Cook, Riggs, Thompson, Coyne, & Sheikh, 2004;Dirkzwager et al, 2005;Mikulincer, Florian, & Solomon, 1995;Riggs, Byrne, Weathers, & Litz, 1998;Solomon, Waysman, Belkin, Levy, Mikulincer, & Enoch, 1992;Whiffen & Oliver, 2004). Recent research on the impact of military deployments to Iraq and Afghanistan since 2003 has found additional support for the negative impact of soldiers' symptoms on spouses' individual symptoms and marital satisfaction (Allen, Rhoades, Stanley, & Markman, 2010;Nelson Goff, Crow, Reisbig, & Hamilton, 2007Renshaw, Rodrigues, & Jones, 2008.…”
mentioning
confidence: 99%
“…Early maltreatment is a traumatic experience that has been consistently linked with increased symptoms of posttraumatic stress disorder among adult survivors (Widom, 1999), which in turn have been associated with poor couple functioning, including increased partner aggression in participants from the community (Taft, Schumm, Marshall, Panuzio, & Holtzworth-Munroe, 2008) and marital dissatisfaction among veterans and former prisoners of war (Cook, Riggs, Thompson, Coyne, & Sheikh, 2004;Dekel & Solomon, 2006). As suggested by these studies, survivors of childhood trauma who are coping with increased trauma symptoms may be so emotionally taxed that they have few remaining resources to devote to working through the stressors that couples encounter in the initial phases of marriage.…”
mentioning
confidence: 99%